INTERNATIONAL LEGAL CO-OPERATION OF THE REPUBLIC OF KAZAKHSTAN IN THE FIELD OF MIGRATION - Maulenov Касым Сырбаевич (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2015)
The article focuses onquestions of international legal regulation of the migration process